Study the Nuclear Structure of 42Ca and 42Ti Mirror Nuclei by Applying the Nuclear Shell Model Using Modified Surface Delta Interaction (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The nuclear shell model was applied using the modified surface delta interaction MSDI tostudy the nuclear structure of the mirror nuclei